2021
DOI: 10.1590/1806-9282.67.01.20200584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two pandemics: H1N1 and SARS-CoV-2

Abstract: OBJECTIVE:We aimed to compare the clinical, epidemiological, and prognostic features of the H1N1 pandemic in 2009 and the severe acute respiratory syndrome coronavirus 2 pandemic in 2020.METHODS: This retrospective study involved subjects from seven centers that were admitted and found to be positive for H1N1 or COVID-19 real-time polymerase chain reaction test.RESULTS: A total of 143 patients with H1N1 and 309 patients with COVID-19 were involved in the study. H1N1 patients were younger than COVID-19 ones. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
1
0
1
Order By: Relevance
“…Em um estudo que fez uma comparação da pandemia de H1N1 em 2009 e da COVID-19 em 2020 ficou demonstrado que os jovens se infectaram mais para o influenza e os idosos foram mais protegidos, e que há rápida disseminação do SARs-CoV-2, e que pode ocorrer mais de uma vez, portanto sugerindo pouca ou nenhuma imunidade. Estes estudos comparativos de pandemias podem servir como ferramentas importantes para traçar estratégias de contenção e manejo de outras pandemias que podem ocorrer 28 .…”
Section: Discussionunclassified
“…Em um estudo que fez uma comparação da pandemia de H1N1 em 2009 e da COVID-19 em 2020 ficou demonstrado que os jovens se infectaram mais para o influenza e os idosos foram mais protegidos, e que há rápida disseminação do SARs-CoV-2, e que pode ocorrer mais de uma vez, portanto sugerindo pouca ou nenhuma imunidade. Estes estudos comparativos de pandemias podem servir como ferramentas importantes para traçar estratégias de contenção e manejo de outras pandemias que podem ocorrer 28 .…”
Section: Discussionunclassified
“…
Dear Editor, We read with great interest the article "Comparison of two pandemics: H1N1 and SARS-CoV-2" by Kant et al 1 In this study, the authors demonstrated that the experience in the HAmg of A/Brisbane/59/2007 (H1N1) pandemic may be the guide to prevent the coronavirus disease 2019 (COVID-19) pandemic from a worse end. This study offers new ideas for the prevention of COVID-19 pandemic.
…”
mentioning
confidence: 96%